The limits to participation: Urban poverty and community driven development in Rajshahi City, Bangladesh. Issue 5 (20th October 2018) - Walters, Peter
ABSTRACT: This article analyzes ways in which urban informal settlements most in need of Community Driven Development (CDD) programs might be overlooked in favor of better functioning poor communities. In a study of two informal settlements in Rajshahi, Bangladesh, one site benefitted from the support of a community based urban poverty reduction intervention from an international donor. The other, poorer, and with greater social challenges, would not qualify. The article highlights the problems the poorest of the urban poor face in developing sufficient community capacity to attract the dominant CDD paradigm of poverty alleviation.